An advanced machining robot flexible programming methodology supported by verification in a virtual environment - Slavković, Nikola; Zivanovic, Sasa; Dimic, Zoran; Kokotovic, Branko (International journal of computer integrated manufacturing, 2025)
The solutions for robot offline programming use different programming environments to facilitate the deployment of robots in machining tasks with the development of specific postprocessors. There is no easy exchange of data between programming software to realise robot machining tasks. This paper presents a flexible programming methodology using several interchange file formats that can be easily exchanged between different CAD, CAD/CAM, or specialised robot programming software. Integrating the standard programming based on CAD, CAD/CAM systems, and STEP-NC protocol through different output files enables data interoperability during the realisation of the robot machining tasks. The developed methodology is proposed for executing programming, verification supported by a virtual environment, postprocessing, and machining by industrial robots. It uses the software for programming machine tools and adapts them to the specifics of robots and their programming languages using a developed postprocessor. The presented methodology enables the programming of robots for 2.5 to 5-axis machining tasks depending on the neutral file format used. Programming verification was realised, first, by simulation on configured virtual robots and developed robot native language editor and, second, by machining on the available robots. These experiments include different contours and shapes and file formats, which show the programming's reliability and accuracy.